2006
DOI: 10.1063/1.2210470
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical and electronic structures of AumAgn (2⩽m+n⩽8)

Abstract: The structural and electronic properties of Au(m)Ag(n) binary clusters (2 < or = m + n < or = 8) have been investigated by density functional theory with relativistic effective core potentials. The results indicate that Au atoms tend to occupy the surface of Au(m)Ag(n) clusters (n > or = 2 and m > or = 2). As a result, segregation of small or big bimetallic clusters can be explained according to the atomic mass. The binding energies of the most stable Au(m)Ag(n) clusters increase with increasing m+n. The verti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 92 publications
6
32
0
Order By: Relevance
“…Its binding energy and bond length reach 2.11 eV and 2.556 Å, respectively. Our theoretical adiabatic ionization potential (9.18 eV) is in reasonable agreement with the experimental data 13 (<9.15 eV), which indirectly supports the reliability of our theoretical calculations. Our theoretical bond length at basis set LANL2DZ(1f) is closer to the experimental observation than those with the basis set LANL2DZ as in Table II.…”
Section: Geometrysupporting
confidence: 88%
See 1 more Smart Citation
“…Its binding energy and bond length reach 2.11 eV and 2.556 Å, respectively. Our theoretical adiabatic ionization potential (9.18 eV) is in reasonable agreement with the experimental data 13 (<9.15 eV), which indirectly supports the reliability of our theoretical calculations. Our theoretical bond length at basis set LANL2DZ(1f) is closer to the experimental observation than those with the basis set LANL2DZ as in Table II.…”
Section: Geometrysupporting
confidence: 88%
“…Theoretical calculations can improve the understanding of geometrical and electronic structures of clusters due to lack of experimentally direct information available at present. Till now, some geometrical configurations of low‐spin mixed gold–silver clusters 10–14 and various isomers of maximum‐spin pure copper clusters 6 have been reported nevertheless the geometrical structures of maximum‐spin gold–silver clusters, especially the position characteristic occupied by exotic heavy or light atoms is still unclear. So our calculations will predict theoretically the structural information of maximum‐spin gold–silver clusters and show different position characteristic of exotic atom from low‐spin situations, which should be useful for future experimental investigations.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] Moreover, the structures of pure gold and silver clusters (Au k , Ag k , k ¼ 1-13) and neutral and anionic gold-silver binary clusters (Au m Ag n (2 k ¼ m þ n 7) have been studied by DFT with generalized gradient approximation (GGA) and high-level ab initio calculations including coupled cluster theory with relativistic ab initio pseudopotentials. 25 More recently, a generic algorithm approach was applied to the optimization of the potential energy of a wide range of binary metallic nanoclusters, AgÀ ÀCu, AgÀ ÀNi, AuÀ ÀCu, AgÀ ÀPd, AgÀ ÀAu, and PdÀ ÀPt, modeled by a semiempirical potential.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to clusters size, the properties of the clusters are dependent on the chemical compositions and arrangement of atoms [1]. Unique and attractive structural [2][3][4][5][6][7][8][9][10][11], electronic [2,3,[9][10][11] and magnetic [12][13][14] properties of the some bimetallic clusters have been reported so far. Also some studies have indicated that bimetallic systems have certain properties that make them better catalysts than pure metals [15][16][17].…”
Section: Introductionmentioning
confidence: 99%